Estádios da Copa do Mundo do Brasil: um estudo de caso de viabilidade econômica do Maracanã - Pismel, Felippe (2017)
This study interprets each soccer game held in Maracanã after a world cup by the end of 2017 as a unique and differentiated product. Even considering an extraction of the maximum income practiced in Monopoly, we did not found economical viability that conciliates rationality with a CAPEX execution of R $ 1.6 billion. In order to run over the breakeven point the requirement of 50 profitable starts, which represents an execution of and unrealistic hypothesis from an economic point of view. It also shows the viability of the poorly designed management model CAPEX, where there is no incentive for clubs to hold their games in the when the public expectation is less than 30 thousand viewers, due to the high operational cost, which refers to the debate on the model of administration of the stadium and a possible concession to the times of football that until the exit. The results suggest that stadium management by football clubs allows for compensation of inefficient matches, below 30 viwers, for efficient matches. More specifically, football clubs are able to control a demand for profits that compensates for inefficient matches. There is also an exclusion of rent from the stadium and a possibility of increasing administrative efficiency by reducing costs.